EFFECT OF KINESIOLOGY TAPING AFTER ROTATOR CUFF TEAR - Bubelis, Justinas; Masiulytė, Ieva (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The purpose of this study was to compare clinical results utilizing two distinct physiotherapy protocols for pain, range of motion and muscle strength. The use of kinesiology tape has become an increasingly popular treatment aimed at reducing musculoskeletal pain and improving function. The novelty of this study is determined by the fact that the effect of physical exercises and kinesiology taping technique on individuals with rotator cuff injuries will be analyzed. Therefore, it was chosen as an intervention applied in conjunction with physiotherapy without kinesiology taping. Keywords: rotator cuff, kinesiology taping, rupture.